Photosynthetic Activity, Yield, Nutrient Use Efficiency and Economics of Rice (Oryza sativa L.) as Influenced by Foliar Supplementation of Urea Phosphate - S.G. Sahu, M. Prusty and P.P. Pradhan, M. Monica, A.K. Dash, N. Panda* (Journal of the Indian Society of Soil Science, 2021)
both nitrogen (N) and phosphorus (P) by plant. Foliar application of UP along with blanket fertilizer doses can influence the photosynthetic activity as well as yield, nutrient use efficiency (NUE) and economics of rice. Hence, a field experiment was conducted in order to study the influence of UP on chlorophyll content, yield, NUE and economics of rice in an acidic Inceptisols of Odisha, India. Different treatments were framed to test the hypothesis as T1: control (no nutrient); T2: 50% recommended dose of fertilizer (RDF); T3: 75% RDF; T4: 100% RDF; T5: 50% RDF + twice foliar spray (FS) of 1% UP; T6: 50% RDF + twice FS of 2% UP; T7: 75% RDF + twice FS of 1% UP; T8: 75% RDF + twice FS of 2% UP; T9: 100% RDF + twice FS of 1% UP and T10: 100% RDF + twice FS of 2% UP. Photosynthetic activity in terms of total chlorophyll content of the green leaves of rice at different growth stages due to different treatments varied from 2.99 to 4.95 mg g-1 fresh weight. Irrespective of treatments, an increasing trend of total chlorophyll content was observed up to 47 days of transplanting and highest content was observed with T10 (4.95 mg g-1 fresh weight). Thereafter, a declining trend in total chlorophyll content was recorded. Plant growth attributes like plant height (107.6 cm) and panicle length (25.7 cm) were recorded highest with T10 treatment. Significantly highest grain (4.58 t ha-1) and straw (5.12 t ha-1) yield of rice were also observed with T10 (100% RDF + twice FS of 2% UP). Highest NUE (57.8 kg of grain kg-1 of nutrient) was recorded with T2, whereas highest agronomic efficiency (15.3 kg of grain kg-1 of nutrient applied) was recorded with T6. Among different treatments, T10 was considered much efficient treatment because of a better benefit cost ratio of 1.74.